Study of gams and related turbulent particle flux with hibp in the T-10 tokamak - Eliseev, L.G.; Lysenko, S.E.; Melnikov, A.V.; Krupnik, L.I.; Kozachek, A.S.; Zenin, V.N. (Вопросы атомной науки и техники, 2017)
The new findings in the behavior of geodesic acoustic modes (GAMs) and turbulent particle flux dynamics on the T-10 tokamak are presented. For the first time in T-10 the broadband oscillations (<250 kHz) of electric potential and density in Ohmic and ECRH regimes (Bt = 1.6…2.4 T, Ipl = 0.15…0.3 MA, n‾e = (0.6…5)×10¹⁹ m⁻³) were measured by Heavy Ion Beam Probe (HIBP) in the core plasmas. At the periphery, at r/a > 0.8, the dominated GAM peak with frequency ~ 14 kHz and noticeable peak of quasi-coherent oscillations in the frequency band 40…100 kHz were observed. The multichannel HIBP measurements were performed to measure poloidal electric field Epol and to retrieve the electrostatic turbulent radial particle flux driven by E×B drift. The preliminary experiment shows that in contrast to the power spectral density of plasma potentials, GAM peak was almost invisible in the Epol power spectrum and on the frequency resolved turbulent particle flux. These results are consistent with the general concept of GAM as a high-frequency branch of zonal flows, having symmetric poloidal structure of potential perturbation, which were supported by earlier observation of poloidal mode number m=0 in T-10. Представлены новые результаты исследований геодезических акустических мод (ГАМ) и турбулентного потока частиц на токамаке T-10. Впервые на Т-10 в разрядах с омическим и ЭЦР-нагревом (Bt = 1,6…2,4 Tл, Ipl = 0,15…0,3 MA, n‾e = (0.6…5)×10¹⁹ m⁻³) в горячей зоне плазмы с помощью зондирования пучком тяжёлых ионов (ЗПТИ) измерены широкополосные колебания электрического потенциала и плотности с частотами до 250 кГц. На периферии, r/a > 0,8, наблюдался преобладающий пик ГАМ с частотой ~ 14 кГц и заметный пик квазикогерентных колебаний с частотами 40…100 кГц. Многоканальные ЗПТИ измерения позволили оценить полоидальное электрическое поле Epol и найти радиальный электростатический турбулентный поток частиц, возбуждаемый E×B дрейфом. Предварительные эксперименты показали, что ГАМ пик виден на спектре колебаний потенциала, но практически не виден на спектре Epolи на частотно разрешённом потоке частиц. Эти результаты согласуются с общей теоретической концепцией, что ГАМ – это высокочастотная ветвь зональных потоков с симметричной полоидальной структурой возмущений потенциала, а также с прежними наблюдениями полоидального модового числа m = 0. Представлено нові результати досліджень геодезичних акустичних мод (ГАМ) і турбулентного потоку часток на токамаці T-10. Вперше на Т-10 в розрядах з омічним і ЕЦР-нагрівом (Bt = 1,6…2,4 Tл, Ipl = 0,15...0,3 MA, n‾e = (0.6…5)×10¹⁹ m⁻³) у гарячій зоні плазми за допомогою зондування пучком важких іонів (ЗПВІ) виміряні широкосмугові коливання електричного потенціалу та щільності з частотами до 250 кГц. На периферії, r/a > 0,8, спостерігався переважаючий пік ГАМ з частотою ~ 14 кГц і помітний пік квазікогерентних коливань з частотами 40…100 кГц. Багатоканальні ЗПВІ виміри дозволили оцінити полоїдальне електричне поле Epol і знайти радіальний електростатичний турбулентний потік часток, збуджуваний E×B дрейфом. Попередні експерименти показали, що ГАМ пік видно на спектрі коливань потенціалу, але практично не видно на спектрі Epol і на частотно дозволеному потоці часток. Ці результати узгоджуються із загальною теоретичною концепцією, що ГАМ - це високочастотна гілка зональних потоків з симетричною полоїдальною структурою обурень потенціалу, а також з колишніми спостереженнями полоїдального модового числа m = 0.